PROJECT-BASED LEARNING IN SCIENCE-SOCIAL EDUCATION AS AN EFFORT TO IMPLEMENT PANCASILA STUDENT PROFILES IN SD MPK BAYAT - Sagita, Raliatifah Hani; Ferryka, Putri Zudhah; Rahmawati, Isna (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
This research was carried out to implement the Pancasila Student Profiles through project-based learning in science learning and analyze students’ abilities in interpreting the Pancasila Student Profiles at MPK Bayat Elementary School, one of the Sekolah Penggerak. This elementary school was established in 2007 as the youngest among the 3 Sekolah Penggerak in the Bayat District. It has 176 boys and 157 girls, organized into 14 study groups. This fact is a challenge in creating students with characters based on Pancasila. The research method is qualitative, where the primary data source is 4th grade students and teachers, and the secondary data source is in the form of publications or journals according to the research theme. The process of collecting data uses observation, interviews and documentation. Once the data is complete, it is reduced, presented and tested. This research found that the application of the Pancasila Student Profiles was carried out through the “Marketday” class project from the Science subject about “economic activities”. In practice, it prioritizes the roles of producers, distributors, and consumers. The application of the Pancasila Student Profiles can be followed by students well, orderly, actively and able to express opinions well. Students are also able to work on projects optimally. Even though in implementation, there are obstacles in the form of student’ lack of attention in the learning process, these obstacles can still be overcome, and during learning activities, students show character according to the Pancasila Student Profiles.